Optimalisasi Fungsi dan Peranan DPRD dalam Pengawasan Kebijakan Penggunaan Anggaran APBD di Kabupaten Pemalang - Aris Ismail; Dendy Patrija W; Zainal Fatah (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2025)
This study examined efforts to optimize the functions and roles of the Regional People's Representative Council (DPRD) of Pemalang Regency in overseeing policies related to the use of the Regional Revenue and Expenditure Budget (APBD). The optimization focused on strengthening the oversight mechanisms, enhancing the technical capacity of the DPRD, and improving inter-institutional coordination to support accountable budget governance. The study was motivated by the persistent weaknesses in legislative oversight, as evidenced by various findings of budget irregularities, including overpayments, misuse of grant funds, and unilateral budget decisions by the executive. A descriptive qualitative approach was used, with data collected through in-depth interviews with members of Commission C, the Budget Committee, and expert staff from the DPRD Secretariat, as well as through document analysis. The findings indicated that the implementation of DPRD’s oversight functions had followed formal mechanisms such as the evaluation of the accountability report (LKPJ) and the discussion of the General Budget Policy and Provisional Budget Ceiling (KUA-PPAS). However, the oversight had not been optimal due to limited access to information, insufficient technical capacity, and weak inter-agency synergy. The DPRD had formulated several optimization strategies, including internal capacity building, the use of digital information systems (SIPD), and strengthening coordination with the Audit Board (BPK) and the regional inspectorate. Therefore, optimizing the DPRD’s oversight function required systemic improvements encompassing institutional capacity, information transparency, and active public involvement in monitoring regional budgets.